2009
DOI: 10.1007/s10562-009-9947-5
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Green Oxidation of Nitrotoluenes with Dioxygen as Oxidant in a Novel Homogeneous and Recyclable Catalytic System

Abstract: A novel homogeneous and recyclable catalytic system was applied in the oxidation of nitrotoluenes to nitrobenzoic acids with the isolated yield of 93%. In this method, the catalytic system could be easily separated from the aqueous phase by simple decantation and could be reused in subsequent runs without apparent change in activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The process was later demonstrated to proceed in an ionic solvent (Scheme 2b). 19 Although slightly higher temperature was necessary, simple acidification of the aqueous layer conveniently provided the pure product and allowed recycling of the ionic liquid solvent, lending the process amenable to large scale industrial applications. Notably, other metal catalysts gave superior results in this transformation and only one substrate was demonstrated with the copper catalyst.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…The process was later demonstrated to proceed in an ionic solvent (Scheme 2b). 19 Although slightly higher temperature was necessary, simple acidification of the aqueous layer conveniently provided the pure product and allowed recycling of the ionic liquid solvent, lending the process amenable to large scale industrial applications. Notably, other metal catalysts gave superior results in this transformation and only one substrate was demonstrated with the copper catalyst.…”
Section: Reactions Of Hydrocarbonsmentioning
confidence: 99%
“…8,9 In oxidative catalysis, dissolved oxygen is used as oxidant for the oxidation of various reagents, such as alcohols, olens, nitrotoluene and cysteine. [10][11][12][13][14][15][16][17][18][19][20] For the latter reaction, Shan et al observed that the performance of the catalyst was directly proportional to the solubility of oxygen and that a higher oxygen concentration resulted in higher yields. Ionic liquids with dissolved oxygen have also been used in metal-free catalytic systems for the depolymerization of lignin model compounds and lignin, 21,22 or as solvent for transition-metal catalyzed oxidation of lignin model compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This signal then disappeared upon addition of 2,4-DNT to the solution. This proved that our system was based on a radical process rather than a mechanism based on a carbon anion under basic conditions [5,7]. Thus, our oxidation system can be applied to a much wider range of substrates, as compared with the literature [5,7].…”
Section: The Mechanism Of the Oxidationmentioning
confidence: 66%
“…For oxidation in our system, the acid yield reached nearly 100%, showing the potential industrial application value of our catalytic system. Additionally, when compared to the literature [5][6][7]13], nitrotoluenes were oxidized successfully into carboxylic acids in this system with yields of almost 100%, which were not affected by the position of the nitro group (runs 3-5). According to the literatures [34,35], the bond energy of m-nitrotoluene is about 2 kJ/mol larger than the p-nitrotoluene.…”
Section: Oxidation Of Other Substituted Toluenes With Strong Electronmentioning
confidence: 77%
See 1 more Smart Citation